STUDENTS’ PERCEPTIONS OF THE CULTURAL APPROPRIATENESS AND SYMBOLISM BEHIND INNER GRADUATION ATTIRE: A COMPARISON BETWEEN INDONESIA AND FOREIGN COUNTRIES - Waruwu, Pujawati; Laoli, Adieli; Harefa, Erlinhartayanti; Zebua, Herianto; Waruwu, Jethrialdo (Widya Mandala Surabaya Catholic University, 2026)
This study examines undergraduate students’ perceptions of the cultural appropriateness, symbolic meaning, and cross-cultural awareness of inner graduation attire in Indonesian graduation ceremonies, particularly in comparison with practices abroad. A descriptive quantitative design was employed, involving twenty undergraduate students from Nias University selected through total sampling. Data were collected using a closed-ended questionnaire consisting of sixteen Likert-scale statements and analyzed by converting responses into percentages categorized as high, moderate, or low perception levels. The findings indicate that students generally hold strong and consistent perceptions regarding the cultural appropriateness and formality of inner graduation attire in the Indonesian context. Traditional clothing such as kebaya and batik is widely regarded as suitable, reflecting respect for academic institutions, cultural norms, and national identity. Participants also recognize the symbolic role of graduation attire in expressing cultural pride and belonging. However, some variation emerges in views of attire as a symbol of academic achievement, suggesting a distinction between symbolic representation and actual performance. Students demonstrate cross-cultural awareness by acknowledging differences between Indonesian and foreign graduation practices while expressing a preference for preserving local cultural values. Given the small, single-institution sample, the findings are context-specific and should be interpreted cautiously